The grey extinction of the ionizing cluster in NGC 3603 from ultraviolet to optical wavelengths - Pang, Xiaoying; Pasquali, Anna; Grebel, Eva K. (Arxiv, 2015)
We use photometry in the F220W, F250W, F330W, F435W filters from the High Resolution Channel of the Advanced Camera for Surveys and photometry in the F555W, F675W, and F814W filters from the Wide Field and Planetary Camera 2 aboard the Hubble Space Telescope to derive individual stellar reddenings and extinctions for stars in the HD 97950 cluster in the giant HII region NGC 3603. The mean line-of-sight reddening for about a hundred main-sequence member stars inside the cluster is $E(F435W-F555W)=1.33±0.12$ mag. After correcting for foreground reddening, the total to selective extinction ratio is $R_{F555W}=3.75±0.87$ in the cluster. Within the standard deviation associated with $E(\rm λ-F555W)/E(F435W-F555W)$ in each filter, the cluster extinction curve at ultraviolet wavelengths tends to be greyer than the average Galactic extinction laws from Cardelli et al. (1989) and Fitzpatrick et al. (1999). It is closer to the extinction law derived by Calzetti et al. (2000) for starburst galaxies, where the 0.2175 $\rm μ m$ bump is absent. This indicates an anomalous extinction in the HD 97950 cluster, which may due to the clumpy dust distribution within the cluster, and the size of dust grains being larger than the average Galactic ISM.